2010
DOI: 10.1007/s10764-010-9412-8
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Song of Indri indri

Abstract: In some primate species, males and females within a social group emit loud calls in a coordinated manner or chorus. Indri indri emits a very conspicuous loud call that elicits the loud calls of neighboring groups. Previous investigations have hypothesized that the main functions of the indri chorus are related to territorial announcement, intergroup avoidance, and group cohesion. We investigated sex differences in indri song. We recorded and analysed songs given by 10 different groups over 160 d. Overall singi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
64
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 37 publications
12
64
4
Order By: Relevance
“…Males, therefore, appeared to produce songs that are overall more similar to those of other males. In agreement with previous studies that reported sexual dimorphism in the overall timing and repertoire size (Giacoma et al, 2010), and in the frequency modulation, duration and rhythm (De Gregorio et al, 2019; Gamba et al, 2016; Torti et al, 2017), we found that male and female indris also differed in the phrase organization of their songs. Female structuring of the song showed a higher number of phrases if compared to males, independently of the phrases being of the same or different type.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Males, therefore, appeared to produce songs that are overall more similar to those of other males. In agreement with previous studies that reported sexual dimorphism in the overall timing and repertoire size (Giacoma et al, 2010), and in the frequency modulation, duration and rhythm (De Gregorio et al, 2019; Gamba et al, 2016; Torti et al, 2017), we found that male and female indris also differed in the phrase organization of their songs. Female structuring of the song showed a higher number of phrases if compared to males, independently of the phrases being of the same or different type.…”
Section: Discussionsupporting
confidence: 93%
“…Cohesion songs were followed by emitters traveling significantly further than following the advertisement song, confirming the different functions of the song uttered in different contexts (i.e., cohesion songs bring together the members of a group, and advertisement songs inform neighbors about the sex, age, and status of singing individuals). Other studies have shown that male and female contributions to the song differ, both quantitatively and qualitatively, in the temporal structure of the units emitted (Giacoma, Sorrentino, Rabarivola, & Gamba, 2010; Sorrentino, Gamba, & Giacoma, 2012). Vocal sexual dimorphism is also present in the modulation of the frequency of vocal utterances, in the duration of unit types and the rhythmic structure of a contribution (De Gregorio et al, 2019; Gamba et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, assuming that individual distinctiveness is related to body size of a specific emitter, F0 appears as a weak parameter for providing individual cues (see Fitch 1997). Moreover, in recent years it has been found that vocal folds are in general very flexible and can vibrate at very different F0s (Riede and Titze 2008), resulting in impressive variation within the repertoire of an individual and of a species (for lemurs: Gamba and Giacoma 2007;Giacoma et al 2010;Maretti et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, functionally referential alarm calls convey information on predator type (Seyfarth et al 1980). Vocal signals can also encode a wealth of cues on individuals' characteristics, such as identity (Maurello et al 2000;Charrier & Harcourt 2006), sex (Rendall et al 2004;Giacoma et al 2010), age/weight , social status (Fischer et al 2004) and behaviour (Jansen et al 2012). However, while many vocalizations will predictably vary with individuals' intrinsic characteristics, these cues may not necessarily be adaptive (Schibler & Manser 2007;Rendall et al 2009).…”
Section: Introductionmentioning
confidence: 99%